Viscous Coefficients of a Hot Pion Gas - Sourav Sarkar (Advances in High Energy Physics)
The steps essentially involved in the evaluation of transport coefficients in linear response theory using Kubo formulas are to relate the defining retarded correlation function to the corresponding time-ordered one and to evaluate the latter in the conventional perturbation expansion. Here we evaluate the viscosities of a pion gas carrying out both the steps in the real-time formulation. We also obtain the viscous coefficients by solving the relativistic transport equation in the Chapman-Enskog approximation to leading order. An in-medium